Posttraumatic stress disorder among emergency ambulance personnel in Baghdad, Iraq - Jacoub, Shirooq M.; Al-Diwan, Jawad K.; Al-Dakhily, Nabeel M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Emergency ambulance personnel (EAP) are vulnerable to PTSD. In Iraq, EAPs were exposed to life threatening situation during political violence conflict post 2003 Gulf war. This study was carried out to report on PTSD among EAP. Patients and Methods: A total of 189 male EAPs were selected randomly from the Dept. of ambulance in Baghdad. A questionnaire form was filled for each EAP. The form included the symptoms of PTSD according to DSM- IV (intrusive, avoidance and hyperarousal symptoms). Demographic data and exposure to violence accident, type of accident and duration of damage were included, also. Results: The mean age of EAP was 38.5 ± 9.4 years. There was 122 (64.5%) had PTSD. Age, education, married status and years in emergency ambulance dept. were significantly associated with PTSD. Conclusion: High rate of PTSD among EAPs was reported. Measures to prevent PTSD and to give further support to EAP are needed. Further studies will clarify the situation of PTSD in Iraq.